Crescimento vegetativo e acúmulo de nutrientes em diferentes genótipos do cafeeiro conilon - Marré, Welington Braida (2012)
The nutrients phenological aspects knowledge is primordial for a better quality and productivity of the coffee. So, the goal of this project was to determinate the seasonable growth and nutrients accumulation by Conilon coffee (Coffea canephora Pierre), along with different periods of maturation and with the orthotropic and plagiotropic branch growth in distinct ages, as well as relate them to climate factors. The experiment was lead between 08/14/2010 and 10/08/2011 in a agriculture rural field, situated on Nova Venécia, Espírito Santo. The principal set lead used in the experiment was completely random, repeated five times. Plants of three years old were utilized, cultivated under full sunshine conditions, with therr meters between lines and one meter between each plant. The growth rate of orthotropic and plagiotropic branches of C canephora are different between distinct kinds of genotypes and they suffer of a seasonable climate variation during the whole year, influenced especially by air temperature variation. Plagiontropic branches along some months and especially with the fruit (coffee) presented lower vegetative growth, compared to newer branches. Distinct genotypes maturation cycle also presented singularities in each absorbed nutrient, varying according to a certain period of time, suggesting, maybe, that each genotype demand a variable quantity of nutrient at the same period. Longer fruit maturation cycles genotypes demand more nutrients and better redistribute them along the cycle. It is suggested that most of Conilon coffee genotypes demand more growth nutrients between mid-September to the second week of May. It is also suggested that fertilizations must be performed in different periods during the year for each kind of maturation cycle, according to nutrient demand for generating the fruit.